On klauder's path : (World Scientific, 1994)
Containing contributions from both mathematicians and physicists, this volume examines Klauder's views on quantum theories, general relativity, optics and chaotic dynamics. A recurrent theme in his research is the role played by coherent states and the so-called "Klauder phenomenon".